Analisis Implementasi Kebijakan Pengelolaan Dana Desa di Desa Pakembinangun, Kecamatan Palem, Kabupaten Sleman - Muhaimin Muhaimin; Yuventus Seran; Kumba Digdowiseiso (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The implementation of the village fund policy is that funds originating from the APBN are earmarked for ordinary villages and villages which are channeled through the APBD to districts/cities to finance state administration, development, and community empowerment and community development. With the enactment of Law Number 6 of 2014 concerning Villages, villages are restored as part of community rights, creating village autonomy, where villages organize government independently, by and for the people. Therefore, all state administrators and village development are expected to be independent, proactive and cooperative. Administration of village finances is a unit that includes planning, implementation, management, reporting and management control. The type of research used is descriptive qualitative research, namely data collected in the form of words, pictures, not numbers. Some of the above phenomena indicate that there are weaknesses in the management and accountability of village funds, thus increasing the demand for implementation of village fund accountability by both the village government and the community. Therefore, this study is considered important to explore the accountability of the village government. In the implementation of Village Funds in Pakembinangun Village, Pakem District, Sleman Regency, there are still several problems. An example is the low absorption or implementation of the village fund budget in Pakembinangun Village or budget absorption that is not in accordance with predetermined targets. Keywords; policy implementation, Management of Village Funds